PENGARUH MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA - Tewika Halawa (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2022)
Education is a process to help humans in developing their potential so that they are able to face any changes that occur. Learning media is one of the useful tools to facilitate the teaching and learning process, in order to streamline communication between teachers and students. Students interest in learning in participating in learning is something important in the smooth teaching and learning process . This study aims to determine the effect of learning media in increasing students' interest in learning. The research method used is a quantitative research method with a descriptive quantitative type. The population in this study were all students at SMA Negeri 1 Onohazumba and the research sample was 57 people. The research instrument uses validity and reliability tests. Data collection techniques using a questionnaire / questionnaire. The data analysis technique uses the regression equation stage , predictive value , coefficient of determination , estimation standard error , regression coefficient standard error , hypothesis testing . The results of this study indicate that using learning media can affect student learning outcomes in economics subjects. This is because, students see directly the object of the material being taught, students are actively involved in learning activities, students understand the concept of the material being taught, students analyze and process information needed individually in solving a problem proposed by the teacher through existing learning media. The suggestions that researchers can convey are that teachers should often use learning media in learning activities because students are more active in learning, students better understand the material being taught and students know themselves the object of the material being taught so that student learning outcomes also increase. Then for students should be involved in learning carried out in class with learning media.